Targeting fidelity of adenine and cytosine base editors in mouse embryos. Issue 1 (December 2018) - Lee, Hye; Willi, Michaela; Miller, Shannon; Kim, Sojung; Liu, Chengyu; Liu, David; Hennighausen, Lothar
Abstract Base editing directly converts a target base pair into a different base pair in the genome of living cells without introducing double-stranded DNA breaks. While cytosine base editors (CBE) and adenine base editors (ABE) are used to install and correct point mutations in a wide range of organisms, the extent and distribution of off-target edits in mammalian embryos have not been studied in detail. We analyze on-target and proximal off-target editing at 13 loci by a variety of CBEs and ABE in more than 430 alleles generated from mouse zygotic injections using newly generated and published sequencing data. ABE predominantly generates anticipated AT-to-GC edits. Among CBEs, SaBE3 and BE4, result in the highest frequencies of anticipated CG-to-TA products relative to editing byproducts. Together, these findings highlight the remarkable fidelity of ABE in mouse embryos and identify preferred CBE variants when fidelity in vivo is critical. Understanding the risks of bystander and off-target editing is essential for genome engineering applications. Here, the authors analyze the fidelity of adenine and cytosine base editors in vivo.